The Influence of Influencer Marketing, Online Customer Reviews, and Online Customer Ratings on Purchase Decisions on the Shopee E-Commerce Platform - Ronald Rose Yangcen; Mahmud Syarif; Desy Tri Anggarini (Riviera Publishing, 2025)
The rapid growth of e-commerce in Indonesia has made Shopee the platform with the highest number of visits in 2023. This study aims to analyze the influence of influencer marketing, online customer reviews, and online customer ratings on Shopee users' purchasing decisions, both partially and simultaneously. The research method uses a quantitative approach with associative design. Data was collected through a questionnaire to 100 respondents who were domiciled in Bekasi and had made transactions on Shopee. The analysis technique used multiple linear regression with the help of SPSS 23. The results showed that influencer marketing (t count = 3,515 > t table = 1,984), online customer reviews (t count = 2,220 > t table = 1,984), and online customer rating (t count = 4,346 > t table = 1,984) had a positive and partially significant effect on purchase decisions with a significance level of < 0.05. Simultaneously, all three variables also had a significant effect (F count = 32.277 > F table = 2.699). Of the three variables, online customer rating is the most dominant factor with a beta coefficient of 0.411. The Adjusted R Square value of 0.487 indicates that 48.7% of the variation in purchasing decisions can be explained by all three independent variables. These findings provide insight into e-commerce businesses in designing more effective digital marketing strategies to increase customer conversions and loyalty.